Odyssey Self Reflection - Chess / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif
When it comes to clean the house, my 3 three siblings would always quarrel. So, my mother had to make a contest to determine who would tidy the house. This fun memory had inspired me to produce my artworks.